Legal gap in legal protection for aggrieved parties at the precontractual stage - Banaba, Hendra; Susilowati, Tri; Sejati, Hono (International Journal Labs, 2024)
This research explores the legal gaps and ambiguities surrounding the principle of good faith in pre-contractual stages, as outlined in Article 1338 paragraph (3) of the Indonesian Civil Code (KUHPerdata). While the principle of good faith is foundational in contract law, its unclear application during negotiations has led to legal uncertainty, potentially disadvantaging parties acting honestly and transparently. The study highlights the need for robust legal frameworks to protect parties from unfair practices and fraudulent actions during the negotiation process. Employing a normative legal research method, the analysis identifies inadequacies in existing regulations and proposes practical reforms, including clearer legal doctrines and amendments to the Civil Code. The findings underscore the importance of good faith at all stages of contractual agreements to foster transparency, fairness, and trust in business relationships, while minimizing disputes and enhancing market integrity. Recommendations for future research include comparative studies on international good faith practices, sector-specific applications, and the integration of technological tools to enforce accountability in pre-contractual negotiations. This work contributes to the development of sustainable and equitable business practices within Indonesian law.